Analisis Perilaku Produsen Batu Alam UD Renta Jaya Campurdarat Tulungagung dalam Perspektif Produksi Islam - Masrur, Imam; Ulfasari, Dwi (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2016)
The natural stones producer’s behavior in production process of UD Renta Jaya causes air and sound pollutions. It is as effect of cutting stones process and truck activities which bringing stones. About the waste, they have initiative to sell it to the colleague. Another cases, they are careless to the employees safety working, examples: employees didn’t use body protector, masker, gloves, etc. On the other hand, based on Islamic production perspective, UD Renta Jaya complies Islamic law purposes (maqasid al-syariah). They use halal material and didn’t contravene with Islamic law. The competition between competitors is faced naturally. They also keep the wise of production and the harmonious of social society by managing the waste, although it is done simply and don’t comply production standard.